KARAKTERISTIK KIMIA SABUN BATANG DARI SUSU SAPI DAN SUSU KAMBING MENGGUNAKAN METODE COLD PROCESS - Gianty Hartani Lugiana; Andri Kusmayadi; Putri Dian Wulansari (JURNAL SAINS PETERNAKAN NUSANTARA, 2022)
Soap is an important non-food requirement in daily needs. Fatty acids that are abundant in cow's milk, namely oleic and palmitic function as cleansers. Casein in cow's milk can be used as a foam stabilizer. The method of making soap in this study uses the cold process method with the advantage that the soap produced has a soft texture compared to other methods. This study aims to determine the effect of using different solvents in soap making on chemical characteristics and to determine which type of solvent produces soap with the best chemical characteristics. This study used a completely randomized design consisting of 3 treatments and 7 replications. The treatment in this study was the use of different solvents, namely P0 (aquadest control), P1 (cow's milk) and P2 (goat's milk). The results of this study indicate that the use of solvents has no significant effect (P>0.05) on the chemical characteristics of milk soap with the cold process method, but the use of solvents for cow's milk soap has a higher foam stability value than goat's milk. Soap with goat's milk solvent has a water content according to SNI less than 15%, namely 11.26%. The use of solvents for cow's milk and goat's milk in the manufacture of bar soap produces soap with a pH value above the bar soap quality requirement, which is 11.46%. Keyword: chemical characteristics, cold process, cow’s milk, goat’s milks, soap